Association of potassium disorders with the mode of death and etiology in patients with chronic heart failure: the INCOR-HF study - Ivna G C V Lima; Jairo T Nunes; Igor H de Oliveira; Silvia M A Ferreira; Robinson T Munhoz; Paulo R Chizzola; Bruno Biselli; Brenno R Gomes; Lucas P Damiani; André S Maria; Fernanda Ronco; Edimar Alcides Bocchi (Scientific Reports)
Abstract Observational studies suggest a U-shaped association between serum potassium (K⁺) levels and mortality in patients with chronic heart failure (CHF). However, the mode of death in patients with HF and K⁺ disorders remains speculative. To investigate the association between potassium disorders and the mode of death in patients with CHF. A retrospective cohort of 10,378 CHF outpatients was analyzed over an average of 3.28 ± 2.5 years. Kaplan-Meier method, Cox proportional hazards regression models, Poisson regression models adjusting for confounders, and e-value determination (e' > 1.6) were used to observe associations between potassium disorders and outcomes. Chagas etiology (p < 0.01) and triple HF therapy (p < 0.01) were associated with hyperkalemia. Atrial fibrillation was associated with hypokalemia (p < 0.01). Chronic kidney disease (CKD) (p < 0.01) and diabetes (p = 0.03) were associated with both. Hypertension was inversely related to hyperkalemia (p < 0.01); age was inversely related to hypokalemia. Associations with mortality were significant for Chagas (p < 0.01, e-value 2.16), stroke (p < 0.01, e-value 1.85), hypokalemia (p = 0.02, e-value 1.94), severe hyperkalemia (p = 0.08, e-value 1.93), and CKD (p < 0.01, e-value > 1.63). Decompensated HF or cardiogenic shock was the cause of death in 54% of patients with normokalemia, 67.8% with hypokalemia, 44.9% with mild hyperkalemia, 57.8% with moderate hyperkalemia, and 69% with severe hyperkalemia. Most patients with hypokalemia and severe hyperkalemia died from decompensated HF (p = 0.007). Data suggest hypokalemia and severe hyperkalemia, along with Chagas and CKD, are associated with death. Unexpectedly, progressive HF was the most frequent mode of death rather than arrhythmias. Further studies are needed to confirm these findings and explore the underlying mechanisms.